A Dominican Sister from Antwerp: Her Bible, Her Memories, Her Prayers - Hoff, Renske (Early Modern Low Countries, 2025)
Maria Ludovica Mortgat, a seventeenth-century Dominican sister, owned a Dutch Bible printed in Antwerp in 1556. On the flyleaf of this Bible, Mortgat made extensive annotations recalling how she entered the convent. She also collected some short prayers and meditations. This case study not only provides insight into textual practice in early modern female convents, but also shows how Bibles were used as paper spaces within which one might develop a sense of religious self. Like the annotations in medieval rapiaria or early modern family Bibles, Mortgat used the blank leaves in her Bible to create a personalised object. In addition, this Bible confirms the relevance of reading Scripture in early modern Catholic contexts.